2013
DOI: 10.5114/jcb.2013.36174
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multi-center dosimetry study of low-dose Iodine-125 prostate brachytherapy performed after transurethral resection

Abstract: PurposeTo evaluate in a multicenter setting the ability of centers to perform pre-implant permanent prostate brachytherapy planning, fulfilling dosimetric goals and constraints based on the Groupe de Curiethérapie-European Society for Radiotherapy and Oncology guidelines in the setting of implantation after prior prostate transurethral resection (TURP).Material and methodsA reference transrectal ultrasound image set of the prostate gland from a patient who had undergone TURP was used. Contouring of the prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…A multi-institutional study comparing 17 centers pre-plans for a single post-TURP patient, showed a propensity to lower doses anteriorly as compared to posteriorly [25]. Neither the previous studies nor our results showed statistical significance of IA quarter metrics as predictors in multivariate models.…”
Section: Discussioncontrasting
confidence: 86%
“…A multi-institutional study comparing 17 centers pre-plans for a single post-TURP patient, showed a propensity to lower doses anteriorly as compared to posteriorly [25]. Neither the previous studies nor our results showed statistical significance of IA quarter metrics as predictors in multivariate models.…”
Section: Discussioncontrasting
confidence: 86%
“…Although other studies have reported that prostate volume also affects D 90 , our study did not find this correlation to be statistically significant, likely because all of our patients had a prostate volume < 50 cc. Previous studies analyzing implant quality have reported a tendency for lower doses to be delivered anteriorly as compared to the posterior prostate in patients treated with LDR brachytherapy [19, 20]. In a multi-institutional analysis of 4547 patients, Merrick et al .…”
Section: Discussionmentioning
confidence: 99%
“…As such, attention to dose painting is critical for tumor control and limiting toxicities. This is especially important for patients at higher risk of significant toxicity, such as those with a history of TURP [28].…”
Section: Discussionmentioning
confidence: 99%